Autonomous motivation mediates the relation between goals for physical activity and physical activity behavior in adolescents. (April 2017) - Duncan, Michael J; Eyre, Emma LJ; Bryant, Elizabeth; Seghers, Jan; Galbraith, Niall; Nevill, Alan M
Overall, 544 children (mean age ± standard deviation = 14.2 ± .94 years) completed self-report measures of physical activity goal content, behavioral regulations, and physical activity behavior. Body mass index was determined from height and mass. The indirect effect of intrinsic goal content on physical activity was statistically significant via autonomous ( b = 162.27; 95% confidence interval [89.73, 244.70]), but not controlled motivation ( b = 5.30; 95% confidence interval [−39.05, 45.16]). The indirect effect of extrinsic goal content on physical activity was statistically significant via autonomous ( b = 106.25; 95% confidence interval [63.74, 159.13]) but not controlled motivation ( b = 17.28; 95% confidence interval [−31.76, 70.21]). Weight status did not alter these findings.